The Influence of Intrinsic Motivation, Non-Physical Work Environment, and Organizational Culture on Job Satisfaction and Its Impact on Work Commitment - Hakim, Abdul; Sugiono, Edi; Nurwulandari, Andini (Riviera Publishing, 2023)
This study aims to determine and analyze the influence of intrinsic motivation, non-physical work environment and organizational culture on job satisfaction and their impact on the organizational commitment of non-government employees at the Ministry of Manpower RI Head Office. The method used in this study is quantitative. The types of data used in this research are primary and secondary. The population used in this study were Government Employees, Non-Civil Servants at the head office of the Ministry of Manpower of the Republic of Indonesia, totaling 416 employees. The results of this study indicate that his study highlights the crucial importance of intrinsic motivation, the non-physical work environment, and organizational culture in shaping job satisfaction and organizational commitment among PPNPN employees. Specifically, intrinsic motivation significantly impacts job satisfaction and organizational commitment, while the non-physical work environment and organizational culture play significant roles in enhancing job satisfaction. Furthermore, job satisfaction itself emerges as a key driver of organizational commitment, emphasizing its significance within the Ministry of Manpower of the Republic of Indonesia, job satisfaction, work commitment.